2003
DOI: 10.1076/jcen.25.7.991.16492
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Normal from Demented Elderly on a Spanish Version of the Verbal Selective Reminding Test

Abstract: The verbal Selective Reminding Test (vSRT) is a frequently used test for evaluating verbal learning and memory. In the present study we investigated the construct validity of a Spanish version of the vSRT by determining its ability to distinguish between a group of healthy elderly subjects and a group of patients with dementia of the Alzheimer type (DAT). Further validation of the test was assessed by comparing the pattern of memory deficits found in the group of patients with DAT with findings from previous n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…In our study, all the depressed patients met the diagnostic criteria for major depressive disorder during the study. Moreover, delayed free recall is considered to be the memory measurement with the greatest sensitivity for the early detection of AD (Swainson et al, 2001), since it is anatomically related to the medial temporal lobe (Campo, Morales, & Martinez-Castillo, 2003). In our study, the percentage of forgetting, which is derived from the delayed free recall score, appeared not to be influenced by the use of antidepressants.…”
Section: Discussionsupporting
confidence: 43%
“…In our study, all the depressed patients met the diagnostic criteria for major depressive disorder during the study. Moreover, delayed free recall is considered to be the memory measurement with the greatest sensitivity for the early detection of AD (Swainson et al, 2001), since it is anatomically related to the medial temporal lobe (Campo, Morales, & Martinez-Castillo, 2003). In our study, the percentage of forgetting, which is derived from the delayed free recall score, appeared not to be influenced by the use of antidepressants.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies have examined average Hispanic-White or English-Spanish differences in neuropsychological tests in community based (La Rue et al, 1999;Rey et al, 1999) and demented samples (Hohl et al, 1999;Loewenstein et al, 1993), and a few studies have compared normal with impaired or demented Spanish speakers (Arnold 628 D. Mungas et al et al, 1998;Campo et al, 2003;Taussig et al, 1996). One study (Mulgrew et al, 1999) examined the relative validity of the Mini-Mental State Examination (Folstein et al, 1975) for detecting cognitive impairment in Hispanics and nonHispanic whites.…”
Section: Discussionmentioning
confidence: 99%
“…Demented patients were compared not only with healthy high functioning control subjects, as in previous studies (Campo et al, 2003;Taussig et al, 1996), but were compared with CIND and with demographically heterogeneous normals. CIND is by definition intermediate to the poles of normal and dementia, and thus creates a challenge to differenate.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish version of the VSRT has been developed and there is some evidence of its reliability and validity (Campo et al, 2000;Campo and Morales, 2004), with significant correlations between form 1 and form 2 that range between 0.65 and 0.72. Campo et al (2003) also found differences between elderly healthy people and patients with dementia of the Alzheimer type using VSRT.…”
Section: Methodsmentioning
confidence: 79%